LIGHT TREATMENT TREATMENT WITH WATER HEAT PARAFFIN THERAPY IN DISEASES OF THE MAXILLOFACIAL AREA (Academicia Globe: Inderscience Research, 2024)
This article delves into the integration of innovative therapeutic modalities—light treatment, water heat therapy, and paraffin therapy—in addressing diseases of the maxillofacial area. Exploring their unique contributions, we examine low-level laser therapy's efficacy in temporomandibular joint disorders, water heat therapy's versatility in trigeminal neuralgia and postoperative care, and paraffin therapy's traditional yet effective role in rehabilitation. The synergistic integration of these modalities offers a comprehensive and patient-centric approach, providing relief from symptoms and enhancing overall well-being. As we navigate this evolving landscape, we anticipate these therapies to play integral roles in mainstream maxillofacial care, contributing to a more nuanced, evidence-based, and personalized treatment paradigm.